SOSIALISASI DISASTER PLAN DAN KESIAPSIAGAAN BENCANA MELALUI VIDEO ANIMASI BAGI PERAWAT PUSKESMAS SE KABUPATEN BANYUMAS - Kamaluddin, Ridlwan; Rahayu, Eva; Wahyu K, Dhadhang; Alivian, Galih Noor (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2022)
Nurses are one of the front lines in handling the COVID-19 pandemic in the health sector. Nurses need adequate knowledge and ability in dealing with disasters. Community nurses in Banyumas Regency are embodied in the INNA Leadership Council Commissariat (DPK) of the Banyumas Regency Health Office. The number of community nurse members is 500 people spread over 40 Puskesmas in Banyumas Regency. Based on the results of the study, as many as 91.2% of community nurses have never attended disaster preparedness training, 52.4% have not had a preparedness plan in the workplace and the level of disaster preparedness of community nurses is at a moderate level. Through this research-based community service program, it is hoped that nurses at Puskesmas throughout Banyumas Regency will gain knowledge regarding the Disaster Plan Health Center as part of disaster risk reduction in their area. This program is carried out through the socialization of the Community Health Center Disaster Plan in the form of virtual animation videos. This online socialization activity consisted of a pre-test of nurses' knowledge about the Community Health Center Disaster Plan, provision of materials, a question and answer discussion and ended with a post test. Animated video socialization activities can increase nurses' knowledge related to the Disaster Plan Health Center. The average value of the pre-test on the puskesmas disaster plan obtained was 68.33, while the post-test score for knowledge about the Puskesmas Disaster Plan obtained an average value of 87.45. Based on the results of the paired t test analysis, it is known that the value (p = 0.00). The results of the analysis indicate that there is a significant relationship or difference between the knowledge scores of nurses at the Puskesmas in Banyumas Regency and the understanding of the Puskesmas Disaster Plan. This Research-Based PKM program has been running smoothly and has resulted in services in the form of providing counseling by experts in the health sector about its functions, components, the process of preparing the Health Center Disater Plan and intellectual property rights, animated videos and publications. Keywords: nurse; disaster preparedness; health center disaster plan